Whitmore’s disease: The great mimicker – A case series (Indian Journal of Case Reports, 2020)
Melioidosis is caused by a Gram-negative bacillus, Burkholderia pseudomallei which resides in the soil and spreads by inoculation, ingestion, and inhalation. Melioidosis is known for its lack of pathognomonic features and sporadic presentation after years of latency. However, it commonly presents with fever, pneumonia, acute septicemia, and abscesses in various internal organs. Although not a drug-resistant organism, its morphological appearance to Pseudomonas, lack of distinct clinical and radiological features, and prolonged therapy pose hurdles in the diagnosis and management. Here, we present a series of four cases admitted to our hospital with pulmonary manifestations of melioidosis, the symptoms of which were subtle and required timely clinical intervention with a microbiological confirmation.